Efficiency of two vaccination schemes against atrophic rhinitis in swine herds - Brito, José R.F.; Mores, Nelson; Brito, Maria Aparecida V.P.; Piffer, Itamar A.; Lorenzetti, Clair (Pesquisa Agropecuaria Brasileira, 2014)
The evaluation of a Bordetella bronchiseptica bacterin for swine atrophic rhinitis (AR) control was carried out in three herds. Prior to vaccination the incidence of nasal turbinate lesions was 89.5% in herd 1; 54.7% in herd 2; and 62.7% in herd 3. There were two treatment groups and one control group within each herd. Treatment A consisted of sows vaccinated at 60 and 100 days of gestation and piglets vaccinated at seven and 28 days of age. The clinical symptoms of AR were observed in 2.7% of the piglets; 12.0% were nasal carriers of B. bronchiseptica; and 28.7% showed turbinate lesions, In treatment B only the sows were vaccinated, at 60 and 100 days of gestation. Six percent of the piglets showed clinical symptoms; 15.4% were nasal carriers of B. bronchiseptica; and 24.8% showed turbinate lesions. In the control group C, the percentages for the parameters described above were 20.0%, 34.3% and 60.3%, respectively. Results indicated that treatments A and B were not statistically different (P>0.05), whereas both were significantly different when compared to control group C (P<0.01). The vaccination against B. bronchiseptica did not confer sufficient protection to eradicate AR in the vaccinated groups, but it did cause a reduction of more than 50% in the incidence of the clinical symptoms, the rate of nasal carriers of B. bronchiseptica and the occurrence and severity of nasal turbinate lesions.